2022
DOI: 10.1111/cogs.13094
|View full text |Cite
|
Sign up to set email alerts
|

What Children with Developmental Language Disorder Teach Us About Cross‐Situational Word Learning

Abstract: Children with developmental language disorder (DLD) served as a test case for determining the role of extant vocabulary knowledge, endogenous attention, and phonological working memory abilities in cross‐situational word learning. First‐graders (Mage = 7 years; 3 months), 44 with typical development (TD) and 28 with DLD, completed a cross‐situational word‐learning task comprised six cycles, followed by retention tests and independent assessments of attention, memory, and vocabulary. Children with DLD scored lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 152 publications
2
28
0
Order By: Relevance
“…This would have been difficult to do in our study because we did not know the other languages spoken by the children before the testing began. Second, recall of semantic features was not sensitive enough to discriminate between children with and without DLD, consistent with the frequent finding that recall of semantic features is easier than recall of phonological information (36,42,102). The higher scores for semantic features could also be explained by the fact that, in our semantic task, the child could see the object and thus easily describe its appearance or say what it was.…”
Section: Limitationssupporting
confidence: 80%
See 1 more Smart Citation
“…This would have been difficult to do in our study because we did not know the other languages spoken by the children before the testing began. Second, recall of semantic features was not sensitive enough to discriminate between children with and without DLD, consistent with the frequent finding that recall of semantic features is easier than recall of phonological information (36,42,102). The higher scores for semantic features could also be explained by the fact that, in our semantic task, the child could see the object and thus easily describe its appearance or say what it was.…”
Section: Limitationssupporting
confidence: 80%
“…They notably require more support using cues ( 40 ) or more retrieval practice (i.e., more naming during the learning ( 41 )) depending on the type of task. These deficits may be explained by difficulties in the initial encoding of the word form-meaning link ( 42 ). They may also be associated with difficulties in short-term memory and executive functions since the word learning performance of children with DLD has been found to be positively correlated with inhibition, verbal short-term memory and verbal working memory ( 37 , 43 ), and it is well know that children with DLD have weaknesses in executive functions ( 44 , 45 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Obeid et al's metaanalysis, already mentioned above (2016), showed that individuals with developmental language disorder (DLD) performed more poorly on statistical learning tasks compared to typically developing controls (g = 0.46, p \ 0.001) (recall that autistic participants did not). Similarly, it has been suggested that word learning difficulties in children and adults with DLD are closely related to encoding the word form, with the pairing of form to meaning and retrieval less delayed (Leonard & Deevy, 2020;McGregor et al, 2020McGregor et al, , 2022. It is not clear that this would be an issue in autism.…”
Section: Atypical Social Communication or Attentional Bias?mentioning
confidence: 99%
“…The raw data, analysis code, plots of data distributions, videotaped examples, and a link to the registration appear in McGregor et al (2020 , OSF | Children’s Vocabulary Project; Remote Communication)…”
Section: Data Code and Materials Availability Statementmentioning
confidence: 99%